Arabidopsis EF‐Tu receptor enhances bacterial disease resistance in transgenic wheat - Schoonbeek, Henk‐jan; Wang, Hsi‐Hua; Stefanato, Francesca L; Craze, Melanie; Bowden, Sarah; Wallington, Emma; Zipfel, Cyril; Ridout, Christopher J (The New phytologist, 2015)
Perception of pathogen (or microbe)‐associated molecular patterns (PAMPs/MAMPs) by pattern recognition receptors (PRRs) is a key component of plant innate immunity. The Arabidopsis PRR EF‐Tu receptor (EFR) recognizes the bacterial PAMP elongation factor Tu (EF‐Tu) and its derived peptide elf18. Previous work revealed that transgenic expression of AtEFR in Solanaceae confers elf18 responsiveness and broad‐spectrum bacterial disease resistance. In this study, we developed a set of bioassays to study the activation of PAMP‐triggered immunity (PTI) in wheat. We generated transgenic wheat (Triticum aestivum) plants expressing AtEFR driven by the constitutive rice actin promoter and tested their response to elf18. We show that transgenic expression of AtEFR in wheat confers recognition of elf18, as measured by the induction of immune marker genes and callose deposition. When challenged with the cereal bacterial pathogen Pseudomonas syringae pv. oryzae, transgenic EFR wheat lines had reduced lesion size and bacterial multiplication. These results demonstrate that AtEFR can be transferred successfully from dicot to monocot species, further revealing that immune signalling pathways are conserved across these distant phyla. As novel PRRs are identified, their transfer between plant families represents a useful strategy for enhancing resistance to pathogens in crops.